HABITUASI REMAJA PECANDU NARKOBA PADA YAYASAN REHABILITASI DHIRA SUMAN TRITOHA - Vini, Dwi Yuniar; Soetrisnaadisendjaja, Denny; Widiansyah, Subhan (Universitas Tanjungpura, 2022)
Social deviations against adolescents are increasingly prevalent because of their curiosity to find identity so that for those who have the wrong association, it will have an impact on social deviations and become drug addicts. While drugs are increasing, there are not many people around to suggest addicts to rehabilitation. This study aims to identify and describe the habituation process of adolescent drug addicts at the stage of Mental, Narcotics, and Geriatrics rehabilitation at the Dhira Suman Tritoha Foundation. This study uses descriptive qualitative research methods, observation, interviews, and documentation techniques. The results of the research in this matter were analyzed using Pierre Bordieu